OCHIQ MATNLI MASALALARNI YECHISHNING KLASTER USULI - Quzmanova, G.B. (SCIENCE and SOCIETY, 2021)
The article examines the importance of the cluster approach in solving open- problems in schools.
Keywords: mathematics; open-problem; cluster; school; problem; solving; teaching; task; education